Song Movement as a Learning Medium: Shape Analysis, MI Mapping, and Teachers' Creative Process at Pertiwi Kutoharjo Kaliwungu Kindergarten - Purhanudin, Viktor; Wulandari, Dewi; Purnomo, Try Wahyu (Journal of English Language and Education, 2026)
This study aims to describe the form of song movement created by Pertiwi Kutoharjo Kaliwungu Kindergarten Teacher, map the elements of song movement to the stimulation of Multiple Intelligences (MI), and explain the creative process of teachers along with the supporting factors and challenges of their implementation at Pertiwi Kutoharjo Kaliwungu Kindergarten. The approach used is descriptive qualitative with a focus on case studies. Data was collected through observation of the implementation of activities, field notes, and study of video documents. The analysis was carried out by summarizing the structure of the musical form and choreography, mapping the MI indicators that appeared during the activity, and then interpreting the findings based on the implementation in the classroom. The results of the study showed that there were three movements of songs created that were used as learning media, namely "Cheerful Morning in My Class", "Ayo Rapi Bersama", and "Lingkar Sahabat". The musical forms and movements exhibit a compact structure with clear repetition; "Cheerful Morning in My Class" tends to be one part (A), "Let's Neat Together" is in the form of A B A, while "Circle of Friends" reads as A1, A2, B, and a coda with an emphasis on floor patterns. MI mapping showed the most consistent musical and kinesthetic tendencies, with linguistic aspects strengthening in songs containing operational verbs, while interpersonal and visual spatial were prominent in songs with circular or semicircular formations. The teacher's creative process takes place through the stages of determining the theme, designing movements, trials, revisions, and routine implementation. The main supporting factors are in the form of classroom routines, audio facilities, collaboration, and school support, while the main challenges are related to space, time, noise, and the heterogeneity of children's abilities. These findings confirm that the design of song movements that are measurable, safe, and easy to remember supports the implementation, safety, and harmony of activities in kindergarten classes.